THE ANALYSIS OF SPEECHNOTE APPLICATION FOR MEASURING THE ACCURACY OF STUDENTS’PRONUNCIATION - Lestari Nurjanah, Sri Eka; Mulyadi, Dodi; Wijayatiningsih, Testiana Deni (Faculty of Humanities, Universitas Jenderal Soedirman, 2019)
Technology, education, and internet have been one of education’s part in this era. Learning independently is one of the choice for many students, not only effective to get understand but also time effectiveness are some of the reasons. All the thing that we learnt in the school is how to improve speaking, listening, writing, and reading skill. That’s why pronunciation become hidden subject which students don’t have to learn it. The problem in our education is English still foreign language for us, so it would be difficult to learn pronunciation autonomuosly or independently. Speechnote is one of the application which was created by WellSource for dictating spoken language to written language with high accuracy. The application helped students to learn pronunciation independently without being watched by the expert. The used method is descriptive-kualitatife and data collective which are recording and filling out questionnaire by 36 participants of students X.IS-1 SMA N 15 Semarang. The result of this research are the error of aplication, the accuracy of recording,recognizing misspronunciation, and the connection of increasing pronunciation by using speechnote.